Pelayanan KTP-el Melalui Aplikasi Whatsapp Di Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Fakfak - Ika Melani; Muhammad Syafei Endro Lareken (Institut Pemerintahan Dalam Negeri (IPDN) Kampus Sumatera Barat, 2022)
The Electronic Identity Card (e-ID) service through the WhatsApp application is a policy on the Fakfak Regency government to prevent the spread of the Corona Disease Virus/Covid-19. Through this service, the WhatsApp application, the community and employees are always protected from crowding and the community is also given the convenience of staying at home even though they want to take care of population documents such as death certificates, identity cards, children’s identity cards, and moving documents. This research was conducted to see and find out how the e-ID service through the WhatsApp is, what the inhibiting factors are and what the efforts of the Population and Civil Registration Agency of Fakfak Regency to overcome the obstacles in e-ID service through the WhatsApp application are. The research method used is grounded theory by means of data collection through observation, interviews and documentation. Based on the results of the research, the authors conclude that the e-ID service through the WhatsApp application at the Population and Civil Registration Service is able to reduce the inhibiting factor by making efforts such as conducting good socialization regarding the benefits of population documents, socializing about e-ID services through the WhatsApp, developing and training for all employees in order to operate all population document publishing services.